Associations between childhood deaths and adverse childhood experiences: An audit of data from a child death overview panel. (April 2019) - Grey, Hannah R.; Ford, Kat; Bellis, Mark A.; Lowey, Helen; Wood, Sara
Abstract: Background: Despite strong associations between adverse childhood experiences (ACEs) and poor health, few studies have examined the cumulative impact of ACEs on causes of childhood mortality. Methods: This study explored if data routinely collected by child death overview panels (CDOPs) could be used to measure ACE exposure and examined associations between ACEs and child death categories. Data covering four years (2012–2016) of cases from a CDOP in North West England were examined. Results: Of 489 cases, 20% were identified as having ≥4 ACEs. Deaths of children with ≥4 ACEs were 22.26 (5.72–86.59) times more likely (than those with 0 ACEs) to be classified as 'avoidable and non-natural' causes (e.g., injury, abuse, suicide; compared with 'genetic and medical conditions'). Such children were also 3.44 (1.75–6.73) times more likely to have their deaths classified as 'chronic and acute conditions'. Conclusions: This study evidences that a history of ACEs can be compiled from CDOP records. Measurements of ACE prevalence in retrospective studies will miss individuals who died in childhood and may underestimate the impacts of ACEs on lifetime health. Strong associations between ACEs and deaths from 'chronic and acute conditions' suggest that ACEs may be important factors in child deaths in addition to those classified as 'avoidable and non-natural'. Results add to an already compelling case for ACE prevention in the general population and families affected by child health problems. Broader use of routinely collected child death records could play an important role in improving multi-agency awareness of ACEs and their negative health and mortality risks as well in the development of ACE informed responses.